2020
DOI: 10.1111/os.12886
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the P53/P21 Pathway Attenuates the Effects of Senescent Nucleus Pulposus Cell‐Derived Exosomes on the Senescence of Nucleus Pulposus Cells

Abstract: The purpose of this paper is to investigate the effects of senescent nucleus pulposus cell (NPC)-derived exosomes (SNPC-Exo) and the roles of the P53/P21 pathway on the senescence of NPC. Methods: The senescent phenotypes of NPC were induced by interleukin-1β treatment. SNPC-Exo was extracted from the culture medium of senescent NPC and purified by differential centrifugation. The structure of SNPC-Exo was identified by transmission electron microscopy and western blot analysis was used to determine the exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The P53 protein is a transcription factor that controls a broad range of cellular processes including cell cycle arrest, DNA repair, and cellular metabolism. The activation of P53 is closely related to the onset of NPC senescence [ 41 ]. Recent study showed activation of Sirt1 might reduce P53 acetylation and potentially protect NP cells against apoptosis and senescence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The P53 protein is a transcription factor that controls a broad range of cellular processes including cell cycle arrest, DNA repair, and cellular metabolism. The activation of P53 is closely related to the onset of NPC senescence [ 41 ]. Recent study showed activation of Sirt1 might reduce P53 acetylation and potentially protect NP cells against apoptosis and senescence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of inflammatory stress in contributing to disc degeneration is well documented, the role of inflammatory stress in disc CS is unclear. Stimulating NP cells with inflammatory cytokines such as IL-1β or TNF-α can induce premature or acute senescence as marked by increased level of SA-β-gal and other senescence markers p16 INK4a , p21 and p53, and loss of proliferation [ 51 , 52 , 53 , 54 ]. In addition, senescent cells induced by TNF-α treatment activate the senescence of healthy cells through phosphorylation of signal transducer and activator of transcription 3 (STAT3) and the paracrine effect via IL-6 secretion [ 55 ].…”
Section: Disc Cell Senescence Under Various Stressorsmentioning
confidence: 99%
“…The level of p16 INK4a expression has also been shown to increase with aging in human disc and animal models of aging [ 8 , 13 , 86 ]. Inflammation induced by TNF-α or IL-1β increases the p16 INK4a , p21 CIP1 , and p53 expression in NP cells [ 51 , 52 , 53 , 54 , 55 ]. In cultured NP cells, a combination of low glucose, hypoxia, high osmolality, and absence of serum induces the expression of p16 INK4a , p21 CIP1 , and intercellular adhesion molecule-1 (ICAM-1) [ 35 ].…”
Section: Signaling Molecules/pathwaysmentioning
confidence: 99%
“…Besides, their enriched exosomal miR-16 could directly inhibit the anti-apoptotic IGF-1/IGF-1R pathway to facilitate the apoptosis of normal NPCs ( Zhang et al, 2021a ; Feng et al, 2022 ). Furthermore, exosomes derived from NPCs with a senescent phenotype induced by IL-1β can accelerate the senescence of normal NPCs by activating the P53/P21 pathway ( Chen et al, 2021 ).…”
Section: Application Of Exosomes and Exosomal Mirnas In Intervertebra...mentioning
confidence: 99%